COMPARISON OF THE EFFECT OF RAMADAN AND INTERMITTENT FASTING PATTERNS ON TRIGLYCERIDE LEVELS IN ELDERLY MALE WISTAR RATS (RATTUS NORVEGICUS) - FITHRIYAH, SAIDATUL; CAHYANI, NABILA K.; MAHMUDAH, NUR; HERNAWAN, BUDI (International Journal of Applied Pharmaceutics, 2025)
Objective: To compare the effect of Ramadan and intermittent fasting patterns on triglyceride levels in elderly male wistar rats (Rattus norvegicus). Methods: This research is a quantitative experimental study conducted in a laboratory setting, utilizing a posttest-only control group design. A total of 18 male rats aged 24 to 25 mo were divided into three groups, namely, K, P1, and P2, with each group containing of 6 rats. K was control group, P1 group fasted according to the Ramadan fasting pattern, and P2 group fasted according to the intermittent fasting pattern, respectively, for 10 consecutive days. The triglyceride levels were analyzed using a spectrophotometer. Results: The highest average triglyceride levels after the intervention were found in P1 group compared to other treatment groups; with the mean value of triglyceride levels was 63.50±22.11 mg/dl. In K group, the average of triglyceride level was 46.83±9.45 mg/dl and in P2 group, it was 60.50±26.09 mg/dl. The results of the comparative analysis between groups using the Kruskal-Wallis test showed the significance value was p = 0.341, so there was no significant difference between groups. Conclusion: Ramadan and intermittent fasting patterns for 10 consecutive days do not have a significant effect on triglyceride levels in elderly male Wistar rats (Rattus norvegicus).